KIMIA OKSIGEN SINGLET: SENSITISER, CAHAYA DAN REAKTIVITASNYA TERHADAP ASAM LEMAK TAK JENUH - Suryanto, Edi (CHEMISTRY PROGRESS, 2008)
Singlet oxygen chemistry and photooxidation reaction, in general, often require one or more criticalreaction steps that involve a sensitizer and light for photochemistry production of singlet oxygen from atriplet state. Singlet oxygen can be formed chemically, enzimatically, and photochemically. However, themost well documented formation mechanism for singlet oxygen is photochemistry using sensitizers.Chlorophyll, riboflavin, myoglobin, porphyrins, erythrosine, rose bengal, methylene blue, bilirubin andretinal are well-known photosensitizer and can absorb energy from light and transfer it to triplet oxygen toform singlet oxygen. Photooxidation provides an important way to produced hydroperoxides fromunsaturated fatty acids in presence of oxygen, light energy and photosensitizer. Hydroperoxide are themajor initiation products of lipid oxidation chain reactions. Singlet oxygen participated in the initiation stepof oil oxidation and the reaction rate of singlet oxygen with oleic, linoleic acid and linolenic are about30.000, 1450 and 900 times greater than that of triplet oxygen. Therefore, this review discusses twoimportant singlet oxygen mechanisms, the formation of singlet oxygen and double bond reaction inunsaturated fatty acid systemÂ Key word: Singlet oxygen, sensitizer, unsaturated fatty acids, hydroperoxides